Research and Development of a Remote Vehicle Diagnostic Device via Mobile Application - Nguyen, Ngoc Le; Nguyen, Minh Khoi; Nguyen, Duy Thong; Le, Thanh Phat; Nguyen, Thanh Tuyen (Journal of Technical Education Science, 2025)
The rapid development of the automotive industry has significantly increased the number of vehicles, thereby driving a higher demand for vehicle diagnosis and maintenance. However, existing diagnostic devices are still limited by their connection range and high cost. This study aims to develop a novel diagnostic solution that offers more flexible and cost-effective connectivity. The research begins by analyzing and synthesizing technical documents on OBD-II systems, android application development tools, and real-time databases. A diagnostic module using an ESP32 microcontroller is then developed to read and process CAN signals from the vehicle's OBD-II system. The module is designed to be compact, cost-effective, and non-intrusive to the vehicle's hardware. Additionally, an android application was developed with functionalities such as data reading, Diagnostic Trouble Code (DTC) reading, clearing all DTC, and component activation testing. This application enables users to interact bidirectionally with the remote diagnostic module via a real-time database without being restricted by distance. The application functions similarly to a multi-functional diagnostic tool, offering effectively unlimited connection range and fast response times (0.4–0.6 seconds). This research successfully delivers a flexible diagnostic solution for vehicles, addressing common limitations of existing diagnostic devices.